Public participation on sustainable development - investigation of the level of sustainable environmental development understanding and awareness - Sumiri, Samsulkamal (2008)
Sustainable development is not a new concept in the scenario of our life as it has been discussed widely in United Nation conferences such as Agenda 21 and Habitat Agenda before been introduced in Malaysia. These development policies encompass three general policy areas: economic; environmental; and social. Malaysia has affirmed its policy on sustainable development in the 7th Malaysia Plan in response to the Agenda 21. This 7th Malaysia Plan describes Malaysia’s ability to develop in sustainable manner. Although there are many policies and campaigns being introduced and implemented, environmental problems still persist and a healthy environment is still continuing detrimental. This research, therefore, deliberated a focus on public participation in sustainable development. The objectives of this research were to identify the level of sustainable environmental understanding and awareness among Malaysian citizens and to identify the barriers that caused the lack of public participation in contributing to development sustainability. The communities of formal education institutions in the state of Johor were approached to get their responses towards the persistence of the sustainable understanding and awareness problems by questionnaires survey. The findings of this research identified the causes of the problems and the proposed solutions from the level of awareness and understanding of the respondents. The recommendation listed provides further enhancement in sustaining Malaysia urbanisation problems. Thus, it would help the concerned parties to take matters into consideration.